Apakah Beban Kerja Mempengaruhi Komitmen Organisasional dan Turnover Intention Perawat? (Journal of Hospital Management, 2020)
Nurse turnover is one of the main problems in hospitals. The 2018 survey report in America revealed data that the total nurse turnover averaged 17.2%. Nurse turnover will cause a shortage of trained nurses and experts in their field. The purpose of this study was to obtain empirical evidence of the effect of workload and workplace spirituality on organizational commitment and nurse turnover intention in MK hospital. This research uses explanatory causal research. Time horizon uses cross section. The sampling technique is convenience sampling. This study uses path analysis, the number of samples is 124 nurses. The results showed that workload, workplace spirituality and organizational commitment simultaneously affected turnover intention; workload and workplace spirituality have a significant positive effect on organizational commitment; workload has a significant positive effect on turnover intention; organizational commitment and workplace spirituality have no significant effect on turnover intention. The findings of the study are turnover intention of nurse is more influenced by workload. While organizational commitment and workplace spirituality do not affect turnover intention. The next findings is that workload and workplace spirituality can increase nurses’ commitment to the hospital. Managerial implications, MK Hospital needs to make a workload analysis, arrange assignment system and make standard amount of workforce. To increase organizational commitment to nurses, MK Hospital can provide challenging work and improve the workplace spirituality of nurses.Keyword: Workload, Workplace Spirituality, Organizational Commitment, Turnover Intention.